Meningkatkan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun Melalui Permainan Galah Asin - Nurjani, Yan Yan; Lestari, Nuri (LP2M STAI Al-Musaddadiyah Garut, 2025)
Based on field observations at KB Ar-Roja, several issues were found related to the development of children's social-emotional skills. One of the problems is the lack of children's attitudes in respecting the rights/opinions/creations of others, and their difficulty in expressing emotions appropriately according to the situation (such as happiness, sadness, or enthusiasm). This research aims to improve the social-emotional abilities of children aged 5–6 years at KB Ar-Roja. One of the inhibiting factors in children's social-emotional development is the monotonous learning activities that are mainly focused on worksheets. The objectives of this research are: to describe the social-emotional abilities of children at KB Ar-Roja; to describe the implementation of the traditional game Galah Asin to enhance young children's social-emotional development; and to describe the improvement in social-emotional skills through the traditional game Galah Asin. This research uses a qualitative approach with a Classroom Action Research (CAR) method. The research subjects are class B students at KB Ar-Roja, consisting of 12 children—6 boys and 6 girls. Data collection techniques used in this study include observation, interviews, and documentation. Based on the observations made by the researcher, before the intervention, the percentage of children showing expected social-emotional development was 16%. After the first intervention cycle, it increased to 58%, and in the second cycle, it rose again to 100%, meeting the criteria of “developing as expected” and “developing very well.” Keywords: social-emotional, Galah Asin